Istiraatiijiyyah Muhaadliri Qismi Ta’lim al-Lughah al-‘Arabiyyah bijaami’ah Tulungagung al-Islamiyyah al-Hukumiyyah fi Tarqiyyah Maharah at-Thullab fi al-Kalamm bil-‘Arabiyyah lil-Am al-Dirasy 2018-2019 M - Iskandar, Nuryani Mansyur (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
This research is a descriptive study by using a qualitative approach. The results of the research are: (1) the methods used by the lecturers of the Department of Arabic Language Education at the State Islamic Institute of Tulungagung to improve students' ability to speak Arabic include: The Power Of Two, Mind Mapping, Audio-Oral method, Task Method; (2) Techniques used by lecturers of the Arabic Language Teaching Department to improve students' speaking skills include: Hifzdul mufradaat (memorizing vocabulary), fahmu al-'madlmuun (understanding the contents of the text), al-Ta'bir al-Muwajjah (guided speaking) , al-Ta'biir al-Hurr (speaking freely), hifdzul al-hiwar (memorizing dialogue texts), al-Tadriibaat wa al-Takrir, al-Sual wa al-Answers; (3) Learning results obtained by the lecturers of the Arabic Language Education Department in improving the students' ability to speak Arabic include: (a) A learning atmosphere (which is conducive), this consists of: students are more active in the learning process, have more interaction and cooperation, more vocabulary mastery, able to achieve maximum learning objectives, (b) The learning value obtained by students is more satisfying.